Deep Eutectic Solvent Micro-Functionalized Graphene Assisted Dispersive Micro Solid-Phase Extraction of Pyrethroid Insecticides in Natural Products - Song, Xiaoyu; Zhang, Rui; Xie, Tian; Wang, Shuling; Cao, Jun (Frontiers in Chemistry, 2019)
Deep eutectic solvent micro-functionalized graphene (DES-G) was synthesized and first applied as the adsorbent of dispersive micro solid-phase extraction (DMSPE) to extract five pyrethroid insecticides. In DMSPE, the target analytes were absorbed by DES-G and then desorbed by trace eluent, next, the treated samples were quantified via ultra-high performance liquid chromatography equipped with diode-array detection. Scanning electron microscope, transmission electron microscopy and Fourier transform infrared spectrometer were used to characterize the prepared DES-G. Furthermore, this method was verified under the selected conditions with the precision ranged from 0.43% to 0.57% for retention times, and repeatability ranged from 0.04% to 2.41% for peak areas. The developed method was successfully applied to determine pyrethroid insecticides residues in beebread, Curcuma wenyujin and Dendrobium officinale with the recoveries in the range of 80.9-114.1%.